THE NATURE OF SEMANTICS - D. Wagiman Adisutrisno (Universitas Muhammadiyah Surakarta, 2007)
With regard to the teaching of semantics, many semantics teachers find difficultyin deciding what to teach in their semantics classes. They have the opinionthat concepts such as connotative meaning, social meaning, affective meaning,collocative meaning, thematic meaning, meaning changes of words, synonymy,antonymy, polysemy, harmonymy, homophony, and homography are the primarymaterials of semantics classes. While those concepts are necessary materials ofsemantics and are usually taught, teachers of semantics must be well aware thatthey are not the primary materials of semantics. They are secondary materials.This paper describes the main materials of semantics which consist of word meaning,sentence meaning, and utterance meaning.